Global analysis of seagrass restoration: the importance of large‐scale planting. Issue 2 (25th November 2015) - van Katwijk, Marieke M.; Thorhaug, Anitra; Marbà, Núria; Orth, Robert J.; Duarte, Carlos M.; Kendrick, Gary A.; Althuizen, Inge H. J.; Balestri, Elena; Bernard, Guillaume; Cambridge, Marion L.; Cunha, Alexandra; Durance, Cynthia; et al.
Summary: In coastal and estuarine systems, foundation species like seagrasses, mangroves, saltmarshes or corals provide important ecosystem services. Seagrasses are globally declining and their reintroduction has been shown to restore ecosystem functions. However, seagrass restoration is often challenging, given the dynamic and stressful environment that seagrasses often grow in. From our world‐wide meta‐analysis of seagrass restoration trials (1786 trials), we describe general features and best practice for seagrass restoration. We confirm that removal of threats is important prior to replanting. Reduced water quality (mainly eutrophication), and construction activities led to poorer restoration success than, for instance, dredging, local direct impact and natural causes. Proximity to and recovery of donor beds were positively correlated with trial performance. Planting techniques can influence restoration success. The meta‐analysis shows that both trial survival and seagrass population growth rate in trials that survived are positively affected by the number of plants or seeds initially transplanted. This relationship between restoration scale and restoration success was not related to trial characteristics of the initial restoration. The majority of the seagrass restoration trials have been very small, which may explain the low overall trial survival rate (i.e. estimated 37%). Successful regrowth of the foundation seagrass species appears to require crossing a minimum threshold of reintroduced individuals. Our study provides the first global field evidence for the requirement of a critical mass for recovery, which may also hold for other foundation species showing strong positive feedback to a dynamic environment. Synthesis and applications . For effective restoration of seagrass foundation species in its typically dynamic, stressful environment, introduction of large numbers is seen to be beneficial and probably serves two purposes. First, a large‐scale planting increases trial survival – large numbers ensure the spread of risks, which is needed to overcome high natural variability. Secondly, a large‐scale trial increases population growth rate by enhancing self‐sustaining feedback, which is generally found in foundation species in stressful environments such as seagrass beds. Thus, by careful site selection and applying appropriate techniques, spreading of risks and enhancing self‐sustaining feedback in concert increase success of seagrass restoration. Abstract : For effective restoration of seagrass foundation species in its typically dynamic, stressful environment, introduction of large numbers is seen to be beneficial and probably serves two purposes. First, a large‐scale planting increases trial survival – large numbers ensure the spread of risks, which is needed to overcome high natural variability. Secondly, a large‐scale trial increases population growth rate by enhancing self‐sustaining feedback, which is generally found in foundation species in stressful environments such as seagrass beds. Thus, by careful site selection and applying appropriate techniques, spreading of risks and enhancing self‐sustaining feedback in concert increase success of seagrass restoration.